Hydrolase-Treated Royal Jelly Attenuates H2O2- and Glutamate-Induced SH-SY5Y Cell Damage and Promotes Cognitive Enhancement in a Rat Model of Vascular Dementia - Nualpun Sirinupong; Worrapanitch Chansuwan; Pratchaya Kaewkaen (International Journal of Food Science)
Vascular dementia (VaD) is the second most common type of dementia following Alzheimer’s disease, but the therapeutic efficacy is still not effective. This makes the searching for novel neuroprotective agents important. Therefore, we hypothesized that royal jelly, a well-known traditional medicine, could attenuate memory impairment and brain damage in vascular dementia. This study determined the effects of royal jelly hydrolysate (RJH) and possible mechanism of cell damage and cognitive-enhancing effect in animal study. An in vitro study assessed the effects of RJH on acetylcholinesterase inhibitor, cell viability, and cell damage in SH-SY5Y neuroblastoma cells. Then, an in vivo study examined vascular dementia by the occlusion of the right middle cerebral artery (Rt.MCAO); adult male Wistar rats had been orally given RJH at doses ranging from 10, 50, to 100 mg/kg for 14 days before and 14 days after the occlusion of Rt.MCAO to mimic the VaD condition. Rats’ spatial memory was evaluated using Morris water maze and radial arm maze every 7 days after Rt.MCAO throughout a 14-day experimental period, and then, they were sacrificed and the acetylcholinesterase (AChE) activity in the hippocampus was determined. The results showed that RJH has no cytotoxic effect with the final concentration up to 500 μg protein/ml and reduces cell death from the H2O2- and glutamate-induced cell damage in in vitro neuroblastoma cells. Importantly, RJH significantly improved memory performance in Morris water maze test and radial arm maze and decreased the level of acetyl cholinesterase activity. In conclusion, RJH is the potential neuroprotective agent and cognitive enhancer for VaD.